PERSEPSI PENGUNJUNG PADA PEMANDU WISATA DI BALAI KERAPATAN TINGGI SIAK SRI INDRAPURA - Afriza, Kamisah; Martina, Elti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to explore more deeply the perception of visitors towards tour guides at the Siak Sri Indrapura High Density Hall. As well as analyzing the duties of tour guides at the High Density Hall which are good duties. The data needed in this study are through several methods, namely direct observation of tour guides at the High Density Hall, questionnaires to visitors and documentation of interviews that will be conducted by researchers to related tour guides. Based on the results of the data analysis, this study shows that visitor perceptions of tour guides at the Siak Regency High Density Hall are good. This can be seen from the question variables about visitor perceptions of tour guides at the Siak Regency High Density Hall which consist of a convincing appearance, pleasant and easy to adapt to the environment and easy to communicate with higher results, namely obtained by the dimensions of pleasant and easy to adapt to the environment with a total score of 1.925, a convincing appearance dimension with a total score of 1.584. And finally the easy to communicate dimension with a total score of 1.076. Keyword: Perception, Visitors, Tour Guides